PENGAWASAN CHEF PASTRY DALAM PENYIMPANAN BAHAN DI PARSTOCK PESONNA HOTEL PEKANBARU - Vivi Andriani; Andri Sulistyani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
Hotel Pesonna has delicious cakes, this is supported by well-done storage and processing. But there are also some errors in its storage. Therefore, storage must always be supervised and supervised, so that material storage is carried out properly so that it can maintain the quality of the material produced and the materials stored can last longer. Pastry chef as the leader in the pasrty room must serve other employees in storing ingredients. This research was conducted to see how the supervision of the pastry chef in the storage of ingredients at the Pesonna hotel Pekanbaru.  Keywords: Chef Pastry, Parstock, Pastry, Hotel